Potential Use of Botanical Termiticide - SUPRIADI SUPRIADI; AGUS ISMANTO (Puslitbang Perkebunan, 2010)
ABSTRACTTermite is one of the most dangerous wood destroying insects and life crop plantations. Termites are commonly controlled using synthetic chemicals which can cause environmental hazzards. However, there are various environmentally methods for controlling termites, including the use of plant extracts and essential oils derived from plants such as orange, clove, and citronella oils. Orange oil has been used quite intensed in the USA, though many questioned concerning the long lasting effect of the oil. The paper is aimed to present general view on the potential use of botanical termiticides and its possible strategy to develop. Various kinds of termites can be found in different ecosystems in Indonesia, such as urban forest trees, plantations, and soils. Synthetic termiticides can be applied as whole treatment and localized treatment. Although the whole treatment is more expensive, but it is more effective because it uses fumigants such as chemicals (sulfuryl fluoride and methyl bromide) or heat. However, these chemicals are known to be ozon depletors. In contrary, the localized treatment is cheaper, but it is less effective and require repetead aplications. The key success in all treatment of termites in any structures is early detection of termite infestation such as signs of damage wood, fecal pellets, and discarded wings. Various plant extracts and essential oils show termiticide activities against different kinds of termites comparable to synthetic termiticide. For example, a formulated botanical pesticide containing clove and citronella oils is effective against dry-wood termite (Cryptotermes cynocephalus). Application of 5% of the formula kill the termite and protect the treated wood almost complete (score 9,8 out of 10) indicating that the formula is potential to be developed. This formula and other potential botanical termiticides need to be evaluated and improved to become more feasible both practically and economically. A main limitation for developing of botanical termiticides is its mass production and its price which can compete with the synthetic ones.Keywords: Termite, essential oil, botanical termiticide ABSTRAKPotensi Antirayap NabatiRayap adalah salah satu serangga perusak kayu paling berbahaya dan juga dapat merusak pertanaman yang masih hidup. Umumnya rayap dikendalikan dengan menggunakan senyawa kimia sintetik yang dapat membahayakan lingkungan, padahal ada cara-cara cara pengendalian rayap yang ramah lingkungan, termasuk penggunaan ekstrak dan minyak atsiri berasal dari tanaman, seperti minyak kulit jeruk (orange oil), minyak cengkeh dan minyak serai wangi. Formula anti rayap dari minyak kulit jeruk sudah dijual di Amerika Serikat, walaupun masih ada kontroversi tentang keefektifannya jangka panjang. Tulisan ini menguraikan kemajuan perkembangan pestisida nabati anti rayap dan strategi pengembangannya. Berbagai jenis rayap ditemukan pada beragam ekosistem di Indonesia, seperti tanaman hutan kota, tanaman perkebunan, dan tanah. Anti rayap sintetik dapat diaplikasikan secara menyeluruh atau secara lokal. Walaupun aplikasi secara menyeluruh lebih mahal biayanya, tetapi lebih efektif, karena menggunakan senyawa kimia fumigan seperti sulfuril fluorida dan methyl bromida atau uap panas. Sayangnya, bahan-bahan kimia tersebut dapat merusak lapisan ozon. Sebaliknya, aplikasi secara lokal lebih murah tetapi kurang efektif dan memerlukan aplikasi ulang. Salah satu kunci keberhasilan pengendalian rayap adalah mendeteksi gejala rayap secara dini, misalnya adanya kerusakan pada kayu, bubuk halus dari kayu yang rusak, dan ditemukannya potongan sayap rayap dewasa. Beragam ekstrak tanaman dan minyak atsiri anti rayap menunjukkan sifat anti rayap yang baik sebanding dengan senyawa anti rayap sintetik. Misalnya, salah satu formula anti rayap berbahan baku minyak cengkeh dan serai wangi menunjukkan dapat mematikan rayap kayu kering (Cryptotermes cynocephalus). Aplikasi 5% formula pada kayu dapat melindungi kayu hampir sempurna (skor 9,8 dari maksimal skor 10). Hasil ini mengindikasikan bahwa formula anti rayap nabati tersebut berpotensi untuk dikembangkan lebih lanjut. Formula tersebut dan beberapa anti rayap nabati potensial lainnya perlu diuji dan diperbaiki sehingga layak baik secara praktis maupun ekonomi. Kendala utama pengembangan anti rayap nabati adalah produksi masal dan harga yang kompetitif terhadap anti rayap sintetik.Kata kunci: Rayap, minyak atsiri, anti rayap nabati.